5‐Aminolevulinic acid has the potential to prevent bladder dysfunction in cyclophosphamide‐induced hemorrhagic cystitis. (18th May 2022) - Kuno, Takahira; Shimizu, Takahiro; Kawada, Chiaki; Kurabayashi, Atsushi; Zou, Suo; Mogawa, Hiroki; Tsuda, Masayuki; Saito, Motoaki; Inoue, Keiji
Abstract : Objectives: To investigate the effects of pretreatment with 5‐aminolevulinic acid hydrochloride combined with sodium ferrous citrate on bladder dysfunction in cyclophosphamide‐induced hemorrhagic cystitis in rats. Methods: Male Wistar rats (340–460 g) were pretreated with vehicle or with 5‐aminolevulinic acid hydrochloride combined with sodium ferrous citrate (100/157 or 300/471 mg/kg/day, po) once daily for 7 days before cystometry. Saline or cyclophosphamide (150 mg/kg, ip) was administered 2 days before cystometry. Cystometry was performed under urethane anesthesia (0.8 g/kg, ip) via a catheter inserted into the bladder. After cystometry, bladder tissues were collected to perform hematoxylin and eosin staining for pathological evaluation (neutrophil infiltration, edema, and bleeding scores), and for enzyme‐linked immunosorbent assay and real‐time polymerase chain reaction for investigating tissue levels of myeloperoxidase, and mRNA levels of haem oxygenase‐1 as a cytoprotective molecule. Results: Compared to controls, cyclophosphamide induced a shorter intercontraction interval, lower bladder compliance, increased number of non‐voiding contractions, and increased pathological scores and myeloperoxidase expression in the bladder. Pretreatment with 5‐aminolevulinic acid hydrochloride combined with sodium ferrous citrate (300/471 mg/kg/day) significantly improved cyclophosphamide‐induced intercontraction interval shortening and increases in number of non‐voiding contractions and neutrophil infiltration/bleeding scores and enhanced haem oxygenase‐1 expression in the bladder. In addition, cyclophosphamide‐induced decreases in bladder compliance and increases in myeloperoxidase were not detected with 5‐aminolevulinic acid hydrochloride combined with sodium ferrous citrate pretreatment. Conclusions: Pretreatment with 5‐aminolevulinic acid expects protective effects on bladder dysfunction in cyclophosphamide‐induced hemorrhagic cystitis by improving inflammatory changes in bladder tissues perhaps via up‐regulation of haem oxygenase‐1.